Circumcision and its potential effects on children's mental health state - YANARTAŞ, ÖMER (ELSEVIER DOYMA SL, 2017)
Objectives: Circumcision is one of the oldest elective surgical interventions in the history of mankind. Though many studies have been conducted on the surgical complications of circumcision, the potential effects on the mental state of the children has not been satisfactorily reviewed. In this prospective study, we analyzed potential effects of circumcision on their mental state, anxiety levels and moods using updated scales. Material and methods: One hundred and two male children aged between 6 and 8 and their families were included in the study. Children with their families completed sociodemographic data form Anxiety Sensitivity Index For Children, the Strengths and Difficulties Questionnaire (SDQ), Depression Scale for Children during the preoperative period. All children received oral 0.5 mg/kg midazolam as a premedication before circumcision procedure. Circumcisions were performed under general anesthesia in the operating room. During the 6th week of the postoperative period, the children and their families were returned to the facility and parents were asked to complete the questionnaire again. Results: Mean score of the preoperative depression scale was statistically and significantly higher than the mean postoperative depression scale score (P=0.001; P<0.01). Pre-, and post-operative depression scale scores of the children with divorced parents showed a higher statistical significance higher than those of the children whose family togetherness was not broken (P=0.001; P<0.01). Conclusion: Before circumcision, in all children to be circumcised a tendency to depression and an increase in anxiety were observed regardless of the presence of subgroups. At the end of the study, it was found that low socioeconomic level, disrupted family dynamic, and/or the presence of mental disease in a parent could increase the predisposition to pre and postoperative depression. At this stage the main factor determining the level of anxiety is the procedure of circumcision itself. (C) 2016 Asociacion Espanola de Andrologia, Medicina Sexual y Reproductiva. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Circumcision; Anxiety; Childhood; Depression; QUALITY-OF-LIFE; PSYCHIATRIC-DISORDERS; PREOPERATIVE ANXIETY; ANTENATAL ANXIETY; COMMUNITY SAMPLE; RISK-FACTORS; PREVALENCE; DEPRESSION; COMPLICATIONS; PREGNANCY